A espada era a lei :visualidades da práxis pedagógica - MELO, Raquel Mendes de (2008)
The insertion of images in the most diverse fields of society has intensified and the educational plan has been a clear source of knowledge, exactly, and potential subjectivities of exploder they provide. As educator (as) the search for improved processes of learning is required of us growing commitment to training and hence to the research in this direction and this work will comply with that role because it was through a deepening of the relationship between images and the subjectivities that they raised as a key to the production of knowledge is that this was necessary for me. Thus, the quest for understanding the educational potential of images and more specifically the moving image in education is the focus of this work in order, to see if the images of the film The Sword was the law raise in teachers visuality of practice teaching, or what would be perceptive of the contributions of each subjective universe (a) one (s) with respect to the visuality of practice teaching in the film